Pengaruh Struktur Modal, Likuiditas, Ukuran Perusahaan dan Profitabilitas terhadap Nilai Perusahaan - Melati, Freshilia Kusuma; Bodroastuti, Tri; Ginanjar, Retno (Jurnal Ilmiah Aset, 2025)
This study aims to determine the influence of Capital Structure, Liquidity, Company Size and Profitability on Company Value. The population in this research is food and beverage companies listed on the Indonesia Stock Exchange in 2018-2022. The sampling method used in this research was a purposive sampling method and a sample of 10 companies was obtained. The data used in this research was obtained from the annual financial reports of food and beverage companies listed on the Indonesia Stock Exchange for 2018-2022. The data analysis method in this research is Multiple Linear Regression analysis. The results of the research showed that simultaneously the variables Capital Structure, Liquidity, Company Size and Profitability had a significant effect on Company Value, partially Capital Structure and Company Size have a positive effect on Company Value while Liquidity and Profitability have a negative effect on Company Value.